John Muir and “Godful” Nature - Raymond Barnett (Religions, 2012)
John Muir, America’s most influential conservationist, held a special view of Nature, one that treated Nature as “Godful” and “unredeemed” because, unlike humankind, Nature has not “fallen”. It is a view that asks us to adopt a gaiacentric, not anthropocentric, perspective on our place in the universe. This article explores the meaning and development of that view and how it came to define Muir’s faith and serve his noble purpose of preserving the Wilderness.